KONTRIBUSI GABUNGAN KELOMPOK TANI DALAM PENGEMBANGAN PRODUKSI KOPI BUBUK RUMAH TANGGA (STUDI KASUS GAPOKTAN MEKAR TANI DI DESA JAMBUWER KECAMATAN KROMENGAN KABUPATEN MALANG) - Ruspina, Monri Nelly; Muljawan, Rikawanto Eko; Mutiara, Farah (Fakultas Pertanian, 2019)
Robusta ground coffee which is often referred to as Jambuwer red coffee itself is produced by the creative hands of Gapoktan and the community in Jambuwer Village. This study aims to analyze the combined contribution of farmer groups in the development of household ground coffee production and determine the relationship of the combined contribution of farmer groups in the development of household coffee production. The research was conducted in the Mekar Tani farmer group Jambuwer Village, Kromengan District. Sampling was carried out using Slovin to obtain 52 people. Methods of data analysis using correlation analysis and data collection, data reduction, drawing conclusions and verification. The results of this study are the contribution of Mekar Tani Gapoktan in the economic and social fields, while the relationship between the contribution of farmer groups has a positive correlation with the development of household coffee production in Jambuwer village that is 0.985 greater than the r table of 0.279 with a significance level of 0,000 < 0.005. Kopi bubuk robusta yang sering disebut dengan Kopi merah Jambuwer sendiri diproduksi oleh tangan kreatif gapoktan dan masyarakat di Desa Jambuwer. Penelitian ini bertujuan untuk menganalisis kontribusi gabungan kelompok tani dalam pengembangan produksi kopi bubuk rumah tangga dan mengetahui hubungan kontribusi gabungan kelompok tani dalam pengembangan produksi kopi bubuk rumah tangga. Penelitan dilakukan di kelompok tani Mekar Tani Desa Jambuwer Kecamatan Kromengan. Pengambilan sampel dilakukan menggunakan slovin sehingga diperoleh 52 orang. Metode analisis data menggunakan analisis korelasi dan pengumpulan data, reduksi data, menarik kesimpulan dan verifikasi. Hasil penelitian ini adalah terdapat Kontribusi Gapoktan Mekar Tani dalam bidang ekonomi dan bidang sosial, adapun hubungan kontribusi kelompok tani memiliki korelasi positif dengan pengembangan produksi kopi bubuk rumah tangga di desa jambuwer yaitu sebesar 0,985 lebih besar daripada r tabel sebesar 0.279 dengan tingkat signifikansi sebesar 0,000 < 0,005.